(untitled) (Ukrainian Journal of Ophthalmology, 2026)
In March 2016, we celebrate the 70th anniversary of the Library at Filatov Eye Diseases and Tissue Therapy Institute, which was founded in 1964 at the direction of academician V.P. Filatov.